Negative appendectomy rate in patients diagnosed with acute appendicitis - Wongsakorn Chaochankit; Aeraungkoon Boocha; Srila Samphao (BMC Surgery, 2022)
Abstract Background Acute appendicitis is the most common cause of acute lower abdominal pain leading patients to the emergency department. This study aims to find the negative appendectomy rate in patients diagnosed with acute appendicitis from 2015 to 2019. Methods This study was a retrospective cohort study in the patients preoperatively diagnosed with acute appendicitis and underwent appendectomy from January 2015 to December 2019. Negative appendectomy is defined as the final pathologic results confirmed normal, congestion or peri-appendicitis. Results The study population was 892 patients which was 54.3% female. The five-year negative appendectomy rate was 8.6% (n = 77) and 70% in female (n = 54). The factors associated with increasing the negative appendectomy rate were female (OR 2.23, P = 0.003), age ≤ 40 years old (OR 2.35, P = 0.003), and no history of diarrhea (OR 2.42, P = 0.017). Whereas the factors related to decline in the negative appendectomy rate were white blood cell count (WBC) $$\ge$$ ≥ 10,000 (OR 0.39, P = 0.016), neutrophil (N) $$\ge$$ ≥ 75% (OR 0.28, P < 0.001), and positive appendicitis from ultrasonography of abdomen (OR 0.04, P < 0.001) or computed tomography of abdomen (OR 0.07, P < 0.001). Conclusion The negative appendectomy rate was less than 10% in this study. Female, age 40 ≤ years old and history of diarrhea were related to increase in negative appendectomy. The factors that related to decline in negative appendectomy were leukocytosis with cells shift to the left, positive acute appendicitis from abdominal ultrasonography and CT scan. However, to request the further imaging studies to diagnose patients with suspected acute appendicitis depends on the risk and benefit to each patient and the choice of investigation.